Outcomes of Laparoscopic Common Bile Duct Exploration by Chopstick Technique in Choledocholithiasis - Suwatthanarak, Tharathorn (JSLS, 2021)
BACKGROUND AND OBJECTIVES: Laparoscopic cholecystectomy with common bile duct exploration (LC with LCBDE) remains the preferred technique for difficult common bile duct stone (CBDS) removal. The chopstick method uses commonly available instruments and may be cost-saving compared to other techniques. We studied the outcome of LCBDE using the chopstick technique to determine if it could be considered a first-choice method. METHODS: Data from all patients that underwent LCBDE from January 1, 2012 to April 30, 2019 were retrospectively analyzed. A standard 4-port incision and CBDS permitted extraction with two laparoscopic instruments by chopstick technique via vertical choledochotomy. Demographic data, stone clearance rate, surgical outcomes, complications, and other associated factors were evaluated. RESULTS: Thirty-two patients underwent LCBDE. The mean number of preoperative endoscopic retrograde cholangiopancreatography (ERCP) sessions was 2.4. In 65.5% of cases, the CBDS was completely removed by the chopstick technique, while 96.9% of stones were removed after using additional tools. The need for additional instruments was associated with increased age, increased numbers of stones, longer period from the latest ERCP session, and previous upper abdominal surgery. The conversion rate to open surgery was 28.1% and was significantly associated with a history of upper abdominal surgery. CONCLUSION: The chopstick technique is a good alternative and could be considered as a first-line technique in LCBDE to remove the CBDS in cases with 1 to 2 large suprapancreatic CBDS due to instrument availability, cost-effectiveness, and comparable surgical outcomes.